Patients' perspective of pathology specimens. A prospective study. Issue 8 (27th July 2005) - Hock, Y L; Balachandar, C; Dicken, S; Bayley, C; Ramaiah, S
Abstract : Aim: To determine the degree of patients' interest in surgical pathology specimens. To assess the impact of patients' involvement in surgical pathology on their understanding of (and confidence in) the storage and use of pathology specimens. Methods: Forty seven patients were invited to visit the pathology department and view their specimens postoperatively. Those who visited were asked to complete a questionnaire to assess the effect of the visit. Results: Thirty three of the 47 patients wished to view their specimens, but only 14 actually made the visit. All those who visited indicated that it made them better able to understand the reason for surgery and tissue retention issues, and more likely to consent to the use of excess tissue for research. Conclusion: In general, patients are keen to know what happens to and what is wrong with the organs removed at surgery, and their involvement in surgical pathology can have positive and beneficial effects both for themselves and the profession.